Electro-biogrouting stabilization of koalin soil - Keykha, Hamed Abdeh (2014)
Biogrouting is a new soil improvement method based on microbiologically induced precipitation of calcium carbonate. Bacteria, which are able to convert urea into ammonium and carbonate, are injected into the soil, followed by a solution containing urea and calcium chloride. Sporosarcina pasteurii is one of the most significant bacteria that hydrolyze urea to carbon dioxide and ammonia by releasing enzyme urease. The calcium carbonate crystals form bridges between the sand grains, which increase the strength of the soil mass. The application of electrical potential between two electrodes in soil has two effects; electroosmosis, the movement of interstitial water toward the cathode; and electromigration, the movement of ionic species, both soluble and particulate. Zeta potential is the potential difference between the dispersion medium and the stationary layer of fluid attached to the dispersed particle. Electrokinetic stabilization is a ground improvement method in which stabilizing agents are induced into soil under direct current. The movement of stabilizing agents into the soil masses is governed by the principles of electrokinetics, while the mechanisms of stabilization can be explained by the principles of chemical stabilization. When ions are used as stabilizing agents, the ions migrate into soils through processes of electro migration and osmotic advection. These ions improve the soil strength by three mechanisms, namely ion replacement,mineralization and precipitation of species in the pore fluid. It is precipitation that provides the greatest contribution to increases in strength. The aim of this study was to use the combination of biogrouting and electrokinetic techniques for injection of bacteria and agents into the kaolin soil to improve soil strength. Firstly, surface electrical properties of two bacillus type strain Sporosarcina pasteurii and Sporosarcina aquimarina , which produce the intracellular urease enzymes were investigated. S. pasteurii is an aerobic soil bacterium while S.aquimarina is anaerobic seawater. The results of zeta potential and electrophoresis mobility (EPM) of both bacteria demonstrated negative surface charge of bacteria in different values of pH. The zeta potential of S. pasteurii was more negative than S.aquimarina. The maximum negative surface charge of S. pasteurii was observed in the pH range of 8.5 to 9.5. The effect of different materials (i.e. NaCl, CaCl2, NH4 + and Urea) on ζ potential of S. pasteurii was studied. The presence of Na+, Ca+2, and urea in the culture media of the bacteria decreased the negative surface charge. Microbially induced carbonate precipitation (MICP) of both bacteria was achieved by varying the concentration of bacterial cells, urea and calcium chloride. The results showed that the S. pasteurii have more activity than S.aquimarina to precipitate CaCO3. The effective laboratory concentrations for MICP were the bacterial cell concentration (B2= 7×108 cells) with a blend of CaCl2 (1M) and urea (1M) for S.aquimarina and CaCl2 (2M) and urea (1M) for S.pasteurii in this study. The greatest amount of CaCO3 was precipitated with concentration of bacteria about 3×108 cells/ml. Secondly, the transport of bacteria in soil specimen (i.e. kaolin) was detected using electrokinetic set up. The result of transportation of S. pasteurii in porous media of fine soil with low permeability demonstrated that the bacteria were moved directly from the cathode to the anode with rate about 6-8 cm/h. The rate of bacteria was increased with the rising current field. Therefore, the bacteria were able to move through soil by electrokinetic technique. Thirdly, A new soil stabilization technique namely electro-biogrouting method (EBM) was developed to improve the soft soil with low permeability. The EBM setup was designed and fabricated at the University Putra Malaysia. The EBM set up consisted of soil container, two injection chambers, pH controllers, mariote bottles, voltmeter, DC power supply. Two methods including the bacteria injection and bacterial products injection were proposed for soil improvement. In the bacterial injection, initially the calcium ions were moved across the specimen by electromigration from the anode to the cathode. Then, the urea, which is non-ionic and solvable, was transported by the electroosmotic flow from the anode to the cathode. Finally, the bacteria with negative surface charge were induced as particles by electrophoresis mobility from the anode to the cathode. The polarity reversal was applied to distribute the bacteria and agents for more uniform precipitation of CaCO3 across the sample. As the bacteria expose the urea, release the urease enzyme and produce carbonate ions resulting of the CaCO3 precipitation in porous media of the soil, and consequently increasing the shear strength. In the second method, the calcium injected into the anode chamber and transported from the anode to cathode by electromigration. Then, the mixed bacteria and urea solution were added to the cathode chamber. The bacteria released enzyme to hydrolyze urea, andthe carbonate (Co3 -2) was produced in the cathode chamber. Then, the carbonate which has a negative charge was moved directly from the cathode to the anode into the soil. Finally, the calcium carbonate was precipitated in the soil, and consequently increasing the shear strength of the soil. After curing for seven days, the results showed that the undrained shear strength of the soil increased from 6 kPa to 65 and 60 kPa for the first and second injection method respectively. Washing acid technique and scanning electron microscope (SEM) confirmed the presence of CaCO3 precipitation ecross the soil sample. The study was important in that it confirmed that the Electro- Biogrouting Method (EBM) is a novel application method of soil stabilization of CaCO3.